Meal Regularity Plays a Role in Shaping the Saliva Microbiota - Viljakainen, Jannina; Raju, Sajan C.; Viljakainen, Heli; Figueiredo, Rejane Augusta de Oliveira; Roos, Eva; Weiderpass, Elisabete; Rounge, Trine B. (Frontiers in Microbiology, 2020)
Background: Diet may influence health directly or indirectly via the human microbiota, emphasizing the need to unravel these complex relationships for future health benefits. Associations between eating habits and gut microbiota have been shown, but less is known about the association between eating habits and saliva microbiota. Objective: The aim of this study was to investigate if eating habits and meal patterns are associated with the saliva microbiota. Methods: In total, 842 adolescents, aged 11-14 years, from the Finnish Health in Teens (Fin-HIT) study cohort were included in this study. Eating habits and breakfast and dinner patterns were derived from a web-based questionnaire answered in school. Three major eating habit groups were identified: fruit and vegetable avoiders (FV avoiders), healthy and unhealthy. Microbiota profiles were produced from 16S rRNA gene (V3-V4) sequencing of DNA from the saliva samples. Statistical models were adjusted for gender, age, parental language, body mass index (BMI) categories, and sequencing depth. Results: Regular breakfast eaters had a higher alpha diversity (Shannon index with mean (standard error of means) 2.27 (0.03) vs. 2.22 (0.03), p=0.06, inverse Simpson’s index with 6.27 (0.17) vs. 5.80 (0.02), p=0.01), and slight differences in bacterial composition (PERMANOVA: p=0.001) compared with irregular breakfast eaters. A similar trend in alpha diversity was observed between regular and irregular dinner eaters (Shannon index with 2.27 (0.03) vs. 2.22 (0.03), p=0.054, inverse Simpson’s index with 6.23 (0.17) vs. 6.04 (0.22), p=0.28), while no difference was found in composition (PERMANOVA: p=0.08). No differences were identified between eating habit groups and saliva microbiota diversity (Shannon index p=0.77, inverse Simpson’s index p=0.94) or composition (PERMANOVA: p=0.13). FV avoiders, irregular breakfast eaters and irregular dinner eaters had high abundances of Prevotella. Conclusions: Regularity of eating, especially breakfast eating, was associated with more diverse saliva microbiota and different composition compared with irregular eaters. However, the dissimilarities in composition were small between regular and irregular breakfast eaters. Our results suggest that Prevotella abundances in saliva were common in FV avoiders and meal skippers. However, the clinical implications of these findings need to be evaluated in future studies.